Seismic Performance Assessment for Serviceability of Geosynthetic Reinforced Embankments - RamazanBorujerdi, Ali (Emerging Advances in Integrated Technology, 2024)
Embankments in the field of civil engineering were historically not given much attention in terms of their ability to withstand seismic activity, as they were considered to be non-critical structures. However, in recent years, the seismic stability of embankments has gained increasing importance in the field of geotechnical engineering. This increased significance is due to the need to quickly restore functional infrastructure after earthquakes. The occurrence of lateral spreading, resulting from foundation liquefaction, is the primary factor leading to embankment distress in geotechnical engineering during seismic events. To address this issue, this study presents a novel approach that employs geosynthetic basal reinforcement. The research paper presents a technique that uses geosynthetic basal reinforcement to manage the lateral spreading of embankments both pre and post earthquakes, guaranteeing their ongoing effectiveness. The proposed approach utilizes a pseudo-static limit equilibrium method for determining the tensile load produced in the basal reinforcement. The serviceability criteria establishes the maximum strain permitted in the basal reinforcement by imposing a restriction on the horizontal movement of the embankment toe. By taking into account the tensile load of the reinforcement and the maximum allowable strain, it is feasible to establish an appropriate geosynthetic reinforcement that considers various factors including tensile strength, strain, design life, installation, and durability impacts.